Direct measurements of the light dependence of gross photosynthesis and oxygen consumption in the ocean. (22nd February 2017) - Bailleul, Benjamin; Park, Jisoo; Brown, Christopher M.; Bidle, Kay D.; Lee, Sang Hoon; Falkowski, Paul G.
Abstract: We measured the light dependence of gross photosynthesis and oxygen uptake rates by membrane inlet mass spectrometry in two open ocean regions: the Amundsen Sea (Antarctica), dominated by Phaeocystis antarctica, and the North Atlantic, dominated by Emiliania huxleyi . In the North Atlantic, respiration was independent of irradiance and was higher than the gross photosynthetic rate at all irradiances. In contrast, in the Amundsen Sea, oxygen uptake processes were light dependent; dark respiration was one order of magnitude lower than the maximal gross photosynthetic rate, but the oxygen uptake rate increased by 10 fold at surface irradiances. Our results suggest the light dependence of oxygen uptake in Amundsen Sea has two sources: one is independent of photosynthesis, and is possibly associated with the photo‐reduction of O2 mediated by dissolved organic matter; the second reflects the activity of an oxidase fueled in the light with photosynthetic electron flow. Our results highlight the importance of improving our understanding of oxygen consuming reactions in the euphotic zone.